KAJIAN ESTETIKA TENUN SONGKET ACEH DI MUTIARA SONGKET KRUENG KALEE DARUSSALAM ACEH BESAR - andini, amanda; ismawan, ismawan; hafid, mukhsin (Jurnal Ilmiah Mahasiswa Sendratasik, 2025)
Aceh Songket weaving is a form of intangible cultural heritage that is rich in aesthetic value and cultural symbolism. However, in the era of textile industry modernization and lifestyle changes, the existence of traditional songket weaving is increasingly under pressure. This study aims to examine and understand the visual elements and design principles in Aceh Songket weaving produced by Mutiara Songket, Krueng Kalee, Darussalam, Aceh Besar, and how these elements shape aesthetic value within the framework of Edmund Burke's concept of The Beautiful and Edmund Burke Feldman's four-stage approach to art criticism. This study uses a descriptive qualitative approach with data collection techniques in the form of direct observation, in-depth interviews, and documentation. The subjects of this study are the craftsmen and owners of Mutiara Songket, while the object is the songket weaving produced. The results show that Aceh songket weaving from Mutiara Songket has harmonious colors, proportionate motifs, symmetrical balance, and consistent visual rhythm. Motifs such as pucok rebong, irih halwa, and bungong peut ulah meurante are not only visually appealing but also contain philosophical meanings that reflect Acehnese cultural values. Thus, Acehnese songket weaving is not only a textile craft product but also a representation of local art with high aesthetic value that is important to preserve.